2021
DOI: 10.1111/dme.14673
|View full text |Cite
|
Sign up to set email alerts
|

Association of type 1 diabetes and educational achievement in 16–20‐year‐olds: A Danish nationwide register study

Abstract: Aims:The objective of the study was to compare grade point averages (GPAs) on compulsory school exit exams (exam GPA) and educational attainment at age 16 and 20 for individuals with and without type 1 diabetes.Methods: This study was a population-based retrospective cohort study, which included the 1991 to 1998 birth cohorts in Denmark. Follow-up was conducted at age 16 and 20 (follow-up period; 1 January, 2007 to 31 December, 2018). There were 2083 individuals with and 555,929 individuals without type 1 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 31 publications
4
11
2
Order By: Relevance
“…Although academic attainment in children and adolescents with T1D has been of research interest, results from prospective studies have been inconclusive. In line with several recent population-based studies, we observed that those with T1D alone had minor academic underachievement and marginally worse compulsory school performance than their healthy peers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although academic attainment in children and adolescents with T1D has been of research interest, results from prospective studies have been inconclusive. In line with several recent population-based studies, we observed that those with T1D alone had minor academic underachievement and marginally worse compulsory school performance than their healthy peers.…”
Section: Discussionsupporting
confidence: 92%
“…One important aspect is educational attainment, which is a determinant for various life course consequences, such as socioeconomic status and overall adulthood health. 9,10 Several populationbased studies [11][12][13][14][15] found that T1D alone was associated with increased risks of school absenteeism, lower examination scores, and adulthood unemployment. However, there remains a distinct lack of studies examining educational outcomes in children and adolescents with comorbid T1D and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Data from Denmark suggest that in young people, type 1 diabetes is associated with a lower grade point average, less school completion and lower participation in higher education, while a lower HbA1c, increased frequency of self monitoring and insulin pump therapy are associated with a higher educational achievement. 8 These associations may be difficult to unpick but highlight that there is a relationship between educational attainment, type 1 diabetes and glycaemia, and that optimising education and glycaemia may be seen as complementary for children and young adults with increased partnership needed between health services and schools. The positive associations between self monitoring, pump therapy and a lower HbA1c with educational attainment suggest that education and support empowering more effective self management may have broader education benefits.…”
Section: Variance Of Concernmentioning
confidence: 99%
“…Childhood with T1DM has been demonstrated to impair brain function in several ways and the brain is metabolically active organ may be affected by glucose instability (13). Chronic hyperglycemia, repeated severe hypoglycemia, and ketoacidosis have all been demonstrated to affect the brain and have an effect on academic outcomes (14). Moreover, T1DM has an impact on practically every aspect of a diabetic child's life, including their cognitive and academic ability.…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, T1DM is linked to decreased neuronal function, which eventually results in cognitive impairment in domains like intelligence, learning, memory, information processing, attention, executive function, visual-motor integration, and academic achievement (6,15,16). According to teacher evaluations and school records in the United States that looked into educational issues in T1DM children discovered that they had lower academic competence ratings, a tendency to pay less attention in class, and more missing school days than their healthy siblings (14,17,18). Furthermore, (17) in Sudan revealed that, T1DM is the most common endocrine disorder in children.…”
Section: Introductionmentioning
confidence: 99%